Radiological and Laboratory Findings of Patients with COVID-19 Infection at the Time of Admission - Saeed Mirsadraee; Mihan Pourabdollah Toutkaboni; Mehrdad Bakhshayeshkaram; Mitra Rezaei; Elham Askari; Sara Haseli; Nazanin Sadraee (Iranian Society of Pathology, 2020)
Background & Objective: Diagnosis of coronavirus disease 2019 (COVID-19) can be challenging, especially when the realtime quantitative reverse transcription polymerase chain reaction (RT-PCR) is not available or it is negative. In this study, we evaluated imaging and laboratory findings in a group of patients with a multidisciplinary diagnosis of COVID-19 pneumonia. Methods: A total of 163 patients with a clinical diagnosis of COVID-19 pneumonia admitted to a specialised respiratory centre in Tehran, Iran were enrolled in this study. The distribution and characteristics of presenting radiological and laboratory findings were evaluated and the relationship to the outcome was investigated. Results: RTPCR was positive in 92 patients. The diagnosis of COVID-19 in RT-PCR negative patients was made on clinical and radiological grounds (n=71). Also, 24 (14.7%) patients died. The common computed tomography (CT) scan findings included ground-glass (94%) and consolidating opacification (12%), mainly in the lower lobes (90%). Peripheral and central lung changes were observed in 90% and 52% of patients, respectively. Lymphopenia, positive CRP, and raised LDH were present in 32%, 65%, and 96% of cases, respectively. A raised LDH of >500U/L was the best predictor of death in these patients (R2=0.6623; OR=24.4). Other markers of outcome were male gender, age (>50 years), lymphopenia, and severe CXR changes. Conclusion: Diagnosis of COVID-19 can be challenging, and a multidisciplinary approach is often needed. Whilst RT-PCR is the standard diagnostic test, a negative test should be interpreted with caution. Blood tests and imaging can be useful in the diagnosis, monitoring, and risk assessment in patients with COVID-19.